2012
DOI: 10.1186/1471-2474-13-225
|View full text |Cite|
|
Sign up to set email alerts
|

A systematic review of the etiopathogenesis of Kienböck's disease and a critical appraisal of its recognition as an occupational disease related to hand-arm vibration

Abstract: BackgroundWe systematically reviewed etiological factors of Kienböck’s disease (osteonecrosis of the lunate) discussed in the literature in order to examine the justification for including Kienböck’s disease (KD) in the European Listing of Occupational Diseases.MethodsWe searched the Ovid/Medline and the Cochrane Library for articles discussing the etiology of osteonecrosis of the lunate published since the first description of KD in 1910 and up until July 2012 in English, French or German. Literature was clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 37 publications
(33 reference statements)
1
27
0
Order By: Relevance
“…In the present study, the internal and external microarchitecture of entire control lunates and lunates with Kienböck's disease has been quantified and compared, in 3D at high resolution. Previous research has focussed on avascular necrosis of other bones such as the scaphoid, or other anatomical sites such as the femoral head, while little has been published on trabecular changes in lunates affected by Kienböck's disease …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the internal and external microarchitecture of entire control lunates and lunates with Kienböck's disease has been quantified and compared, in 3D at high resolution. Previous research has focussed on avascular necrosis of other bones such as the scaphoid, or other anatomical sites such as the femoral head, while little has been published on trabecular changes in lunates affected by Kienböck's disease …”
Section: Discussionmentioning
confidence: 99%
“…Kienböck's disease is idiopathic lunate bone osteonecrosis, leading to lunate fracture and carpal collapse. The aetiology of Kienböck's disease is poorly understood, with intrinsic and extrinsic factors likely to contribute. Reported intrinsic factors are negative ulnar variance, excessive radial inclination, trapezoidal lunate shape and lunate trabecular orientation, as well as variations in vasculature .…”
mentioning
confidence: 99%
“…A negative ulnar variance (UV), primary arterial ischemia, trauma, and hand-arm vibration are considered possible risk factors for Kienböck's disease, and among these risk factors, negative UV appears to be the most commonly reported risk factor. 2 In fact, since Hulten first reported the relationship between negative UV and Kienböck's disease, 3 several studies have confirmed this relationship. [4][5][6][7] However, some studies have reported contrasting results.…”
Section: Introductionmentioning
confidence: 98%
“…Among the most important reasons discussed in the literature so far, negative ulnar variance, arterial ischemia, trauma and occupational factors are considered as the etiology of KD more than others (2). Nevertheless, none of these factors is proven or rejected.…”
Section: Introductionmentioning
confidence: 99%